PENGARUH BEST PRACTICE DALAM PELAKSANAAN KURIKULUM MERDEKA TERHADAP PEMBENTUKAN KARAKTER PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI SISWA KELAS VII DI SMP NEGERI 2 ABIANSEMAL BADUNG - Widiasanti, Ni Made; Anggreni, Ni Made; Muliani, Ni Made (Guna Widya: Jurnal Pendidikan Hindu, 2025)
The implementation of Merdeka Curriculum in Indonesia is a progressive step in the world of education that aims to create a more flexible and student-centered learning environment. This curriculum is designed to give schools and teachers more freedom in developing and implementing learning that suits the needs and potential of students. In this context, the implementation of Best Practices is very important to ensure the success and effectiveness of this curriculum. One of the schools that implement Merdeka Curriculum and Best Practice is SMP Negeri 2 Abiansemal Badung, especially for grade VII students, this Merdeka Curriculum was implemented in 2023. This study aims to examine the effect of Best Practice in the Implementation of the Merdeka Curriculum on Character Building in Hindu Religious Education and Budi Pekerti subjects for seventh grade students at SMP Negeri 2 Abiansemal Badung. This research is quantitative research with experimental research type. The method used in this research is Quasi Experiment (pseudo experiment), in this study, samples were placed in experimental groups and control groups. The population of this study were all seventh grade students at SMP Negeri 2 Abiansemal Badung with the sampling technique of simple random sampling. Data analysis techniques used are descriptive and inferential analysis techniques. The results showed that there was a significant effect of implementing Best Practice in the implementation of the Merdeka Curriculum on character building in the subject of Hindu Religious Education and Budi Pekerti for seventh grade students at SMP Negeri 2 Abiansemal Badung. The Education Office along with teachers, students, and parents must be able to work in the development of this independent curriculum. Keywords: Best Practice, Independent Curriculum, Character Building, Hindu Religious Education and Budi Pekerti.